Dynamics of tensegrity solar FaÇades operating as mechanical energy harvesters - Miranda, Raffaele (2022)
Funding Information: R.M., N.S., and F.F. acknowledge financial support from MIUR under the PRIN 2017 National Grant ‘Multiscale Innovative Materials and Structures’(grant number 2017J4EAYB).